PENGARUH PENGEMBANGAN KOMPETENSI KARIER DAN DUKUNGAN SOSIAL TERHADAP KEBERLANJUTAN KARIER FREELANCER DI INDONESIA DENGAN EFIKASI DIRI SEBAGAI VARIABEL INTERVENING - Sasa Dwi Pramita; Mukhroji Mukhroji (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study examines the phenomenon of the increasing number of freelancers in Indonesia driven by layoffs and changes in the labor market, while highlighting key challenges such as independent career competency development, limited social support, and low self-efficacy. Using a quantitative approach, this study aims to examine the effects of career competency development and social support on freelancers’ career sustainability, with self-efficacy as an intervening variable. The research sample consisted of 385 active freelancers selected using convenience sampling. Data analysis was conducted using Structural Equation Modeling (SEM) through SmartPLS 4. The results indicate that career competency development and social support have a positive direct effect on career sustainability and self-efficacy. In addition, self-efficacy was found to mediate the indirect effects of career competency development and social support on the career sustainability of freelancers in Indonesia. These findings emphasize the importance of competency development, social support, and self-belief in building sustainable and adaptive freelance careers in the context of the modern labor market in Indonesia.